2003
DOI: 10.3127/ajis.v10i2.156
|View full text |Cite
|
Sign up to set email alerts
|

Student Use of the Internet: an extension of TAM in technical and vocational institutions in Brunei Darussalam

Abstract: In the educational setting, the Internet is profiteering among academics and students. In fact, this has changed the functioning of the educational establishments. However, the success of use of the Internet is largely dependent upon the user's behaviour that in turn affects their attitudes. Even when the formidable opportunities exist for the deployment of technology, adverse attitude can inhibit the use. Keeping this in view, survey of 266 students of four technical and vocational colleges was conducted to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…The results are consistent with the findings of Cronan, Foltz and Jones [27], Malin and Fowers [44], and Seyal and Rahman [45]. They reveal that the longer a student has used a computer, the greater his/her intention to pirate software.…”
Section: Personal Computer Experiencesupporting
confidence: 82%
See 1 more Smart Citation
“…The results are consistent with the findings of Cronan, Foltz and Jones [27], Malin and Fowers [44], and Seyal and Rahman [45]. They reveal that the longer a student has used a computer, the greater his/her intention to pirate software.…”
Section: Personal Computer Experiencesupporting
confidence: 82%
“…Students who do not have much experience of computer use are more likely to use a computer only for what their tasks and assignments require [40]. Cronan, Foltz and Jones [27], Malin and Fowers [44], and Seyal and Rahman [45] found that the more familiar a student is with a computer, the more likely the student will be to pirate software. In contrast, Kini, Ramakrishna and Vijayaraman [43] found that the relationship between experience and piracy was insignificant.…”
Section: Personal Computer Experiencementioning
confidence: 99%
“…Later, TAM re-established BI's direct dependence on UA. Several IS studies have provided empirical evidence supporting such a relationship (Seyal and Rahman 2003). For example, Kuo and Yen (2009) found that UA is the most influential factor for BI to use 3G mobile value-added services, while Xu, Oh, and Teo (2009) (2005) found BI to be a factor significantly affecting AU.…”
Section: User Attitude Behavioural Intention and Usage Behaviourmentioning
confidence: 97%
“…PEoU is defined as the degree to which a person believes that using a technology will be free from effort (Davis 1989). PEoU has been a widely-used variable in IS/IT studies, including those on the Internet (Bradley 2012, Jebeile and Reeve 2007, Seyal and Rahman 2003, m-commerce (Yang 2005), and mobile services (López-Nicolás, MolinaCastillo, andBouwman 2008, Nysveen, Pedersen, andThorbjørnsen 2005b). PEoU has also been identified as a significant factor for location tracking and location awareness services .…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…5, No. 8, August 2015 610From an academic perspective, studies have been conducted in Brunei Darussalam using TAM to determine the Internet use among students [18], senior executives [19] and business managers [20]. Studies were also undertaken on e-learning adoption among students and academic staff of an institution of higher learning focusing on TRA [21], [22].…”
mentioning
confidence: 99%